Proceedings of the 2000 ACM SIGMOD International Conference on Management of Data 2000
DOI: 10.1145/342009.335423
|View full text |Cite
|
Sign up to set email alerts
|

A framework for expressing and combining preferences

Abstract: The advent of the World Wide Web has created an explosion in the available on-line information. As the range of potential choices expand, the time and effort required to sort through them also expands. We propose a formal framework for expressing and combining user preferences to address this problem. Preferences can be used to focus search queries and to order the search results. A preference is expressed by the user for an entity which is described by a set of named fields; each field can take on values from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 6 publications
0
82
0
Order By: Relevance
“…Although the role of the preferences was recognized in applications long ago, the database researchers paid attention to this issue only around year 2000 [17,18,19,20]. It was observed that in database queries WHERE-conditions are hard constraints and either the non-empty result set is returned if all the conditions are satisfied, or an empty set is returned in the opposite case.…”
Section: A Closer Look At User Preferences: Hard and Soft Constraintsmentioning
confidence: 99%
“…Although the role of the preferences was recognized in applications long ago, the database researchers paid attention to this issue only around year 2000 [17,18,19,20]. It was observed that in database queries WHERE-conditions are hard constraints and either the non-empty result set is returned if all the conditions are satisfied, or an empty set is returned in the opposite case.…”
Section: A Closer Look At User Preferences: Hard and Soft Constraintsmentioning
confidence: 99%
“…In quantitative approaches, each preference is associated with an atomic scoring function, and combination operations are used to compute a score for each result tuple [12]. This restricts the approach to total orderings of result tuples.…”
Section: Querying With Preferencesmentioning
confidence: 99%
“…Indeed, over the years, several proposals enhancing the query capabilities of relational systems have been made. Recent examples include preference queries, which incorporate qualitative and quantitative user preferences [1,3,13,8,17] and topqueries [10,9,2].…”
Section: Permission To Copy Without Fee All or Part Of This Materials mentioning
confidence: 99%
“…Such queries are introduced as a novel query type seeking to provide greater query flexibility on top of relational data sources. Recently proposed, but not directly related, query types include preference queries [1,12,3,13,8,17] and top-k queries [10,9,2].…”
Section: Related Workmentioning
confidence: 99%